Antifungal resistance does not necessarily affect Candida glabrata fitness. (February 2014) - Borghi, Elisa; Andreoni, Stefano; Cirasola, Daniela; Ricucci, Valentina; Sciota, Rita; Morace, Giulia
Abstract : Although there has been an overall good coverage of Candida glabrata infections by the echinocandins, emergence of antifungal resistance during therapy has been reported. We investigated, by using an invertebrate host model, the fitness of sequential C. glabrata isolates with different echinocandins susceptibility patterns. The studied strains were isolated from a case of recurrent fungemia with a fatal outcome due to C. glabrata that developed cross-resistance to echinocandins during caspofungin therapy. The sequential strains isolated post-therapy showed a S663P mutation in the Fks2p hot spot 1. In vivo study in the invertebrate host Galleria mellonella did not suggest a fitness cost related to the acquired antifungal resistance, the three isolates displayed a similar rate of killing ( P = 0·54). We observed a clear correlation between emergence of antifungal resistance and persistence of the causal agent, probably aided by the unchanged fitness and unresponsiveness in vivo to the adopted therapy.